Variation features of the mean sea water level in Nha Trang bay - Chung, Tran Van; Long, Bui Hong; Hoan, Pham Sy; Tuan, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2019)
Analysis of sea water levels (SWL) data at the Cau Da Oceanographic Station for 42 years (1975–2016) showed that the rising trend of SWL had occurred from 1999. During the 42-year period, the annual mean SWLs were lowest in 1988 and 1998. The recorded special feature showed that since 2006 (2006–2016) the annual mean SWLs were above the longtime mean SWL especially during Northeast Monsoon period. The years of 1979, 1983, 1984, 1987, 1988, 1992 showed the annual mean SWLs were higher than that of longtime mean SWL. And the years of 1978, 1994, 1998 showed the annual mean SWLs coinciding with longtime mean SWL